Unbound: An Origin Story - Moshayov, Guy (Michaelis School of Fine Art, 2025)
In Unbound, I embark on a semi-autobiographical quest, through which I reflect on the subject of a ‘myth of origin'. I rely on the two foundational yet competing epistemes that have been shaping my understanding of the concept throughout my life: On one end, the dogmatic Abrahamic mythology with which I was raised as an Israeli Jew; On the opposing end, Darwin's theory of evolution, as laid out in On The Origin of Species, which gradually came to replace many of my childhood's traditional narratives. In a body of work comprising a graphic novel and a series of large-scale oil paintings, the Darwinian and Abrahamic stories clash, bend, and blend. Unbound is the practice of reflexive doubt. While this project exists in an academic sphere, I refrain from calling it ‘research' in the traditional sense of the word. Rather, I choose to frame my academic practice as ‘artistic inquiry', for it is aimed at asking critical questions, rather than providing definitive answers. For this end, I generate a lexicon of visual iconography, a strategy which, in the words of art scholar Daniel Morris, enables the work to live between ‘public history and private myth'. I draw from an array of influential Jewish artists who have utilized this strategy effectively, among which are Philip Guston, William Kentridge, Dana Schutz, Will Eisner, and Art Spiegelman. According to Morris, relating to public history through the use of a private lexicon provides the work a germinative property which enables it to outlive the time in which it was created. Unbound aims to obtain this very same effect.